KEANEKARAGAMAN JAMUR TANAH DI KAWASAN KEBAKARAN HUTAN GUNUNG LAWU, MAGETAN, JAWA TIMUR TAHUN 2015 - Rahabistara Sumadji, Angga (Widya Warta, 2017)
The forest fire in Mount Lawu by 2015 can cause biodiversity in the forest and alter the wealth of the soil chemical physics affecting the soil microbial composition. This study was aimed at examining the diversity of soil fungi in the forest area of Mount Lawu which had undergone fire. The soil sampling was conducted in the formerly burned area, namely in block 63 in the back of post 2 Cemoro Kandang, Karanganyar, Central Java. The data analysis used was descriptive. The results showed that the soil fungi isolated successfully in four soil sampling sites amounted to 4 species. The four species were Aspergillus sp, Doratomyces purpureofuscus, Cephalotrichum sp and Alternaria alternata.